Publications of the Journal Nursing in New Dimensions (1975-1979): traces of care to newborns - Isis Vanessa Nazareth; Edilaine Rocha Vieira de Oliveira; Wellington Mendonça de Amorim; Inês Maria Meneses dos Santos; Leila Rangel da Silva (Rev Rene)
One aimed to identify and analyze the nursing scientific production about maternal and child health published in the journal Nursing in New Dimensions. This is a historical study with documentary analysis carried.As the primary source,27 issues of the journal Nursing in New Dimensions were used. Those thataddressed newbornswere included. The organization of data occurred through three figures. One included 12 articles in the study analyzed through three analytical categories: Nursing Health Care to Hospitalized Children; Concerns with Children’s Well-being; Encouragement for Research in Nursing. The subjects covered in the magazine seemed to herald a new dimension to the Brazilian nursing, in this case, the possibilities of performance in the maternal and child health area.